Changes in the prevalence of child marriage in Ethiopia, 2005-2016 - Annabel Erulkar (BMC, 2022)
Plain Language Summary Child marriage has powerful implications for young women's reproductive health, education, and welfare. Using data from Ethiopia Demographic and Health Surveys for 2005, 2011, and 2016, this paper analyzes subnational trends in child marriage over the last decade. Between 2005 and 2016, the percentage of Ethiopian women married before age 18 declined from 49 to 40%, a reduction of 18%. The percentage of women married before age 15 experienced even greater reductions, declining by 26% in the same period. The greatest reductions in child marriage took place in Addis Ababa, Amhara, and Tigray regions. Over the same period, estimates for Oromia and Somali regions suggest that child marriage has increased in these regions. Afar, Beneshangul-Gumuz, Somali, and Oromia are regions where more than or nearly half of all girls are married before age 18. Nationally, Ethiopia has experienced impressive declines in child marriage over the last decade. However, progress has also been uneven, resulting in a geographical shift in where child marriage is most prevalent. Remote and hard-to-reach locations pose persistent challenges to eradicating child marriage. Intensifying efforts in rural areas and underserved regions can achieve the elimination of child marriage in Ethiopia.